Widespread coral bleaching and mass mortality during the 2023–2024 marine heatwave in Little Cayman - Matthew L. Doherty; Jack V. Johnson; Gretchen Goodbody-Gringley (PLoS ONE, 2025)
The increased frequency and intensity of marine heatwaves (MHWs) induced by continued global warming are the greatest threat to tropical coral reefs, causing mass bleaching events and widespread mortality of reef building corals. In 2023, the isolated and well-protected reefs around Little Cayman experienced a MHW of > 17 Degree Heating Weeks (DHW), far exceeding any DHW measure previously captured. During the peak of the heatwave, ~ 80% of all corals were either bleached or showing signs of mortality. On the final survey date ~54% of all corals surveyed were recorded as dead. However, we identified significant differences in bleaching susceptibility and mortality across taxonomic groups, related to different life history strategies. Notably, weedy coral taxa such as Agaricia spp., Porites astreoides, and Porites porites, experienced high bleaching and suffered extensive mortality. Meanwhile, stress-tolerant reef building taxa such as Orbicella spp., experienced bleaching, but suffered low mortality. Given Little Cayman reefs have not been exposed to previous thermal stress events, the highly sensitive weedy taxa disproportionately contributed to coral abundance. Thus, the occurrence of a high magnitude – long duration heatwave resulted in catastrophic mortality of corals in Little Cayman, despite ~57% of the coastal environment being classified as no-take Marine Protected Areas. These findings underscore that the global stressor of global climate change, which drives MHWs, cannot be mitigated by local protection and isolation, thus highlighting the need to directly tackle the cause of coral decline (i.e., global climate change).